Mechanisms of Cellular Adaptation and Change: A Narrative Literature Review - Hidayat, Rachmat; Catherine (Open Access Indonesian Journal of Medical Reviews, 2023)
Injury to cells and the surrounding environment, called the extracellular matrix, triggers injury to tissues and organs. Although a normal cell is limited by narrow boundaries of structure and function, it is capable of adapting to biological demands or stress to maintain a steady state called homeostasis. Adaptation is a reversible, structural, or functional response to normal or physiological conditions and adverse or pathological conditions. This review aimed to describe the mechanism of cellular adaptation in the human body. Cells adapt to the environment to escape and protect against injury. Adaptation of the cell, be it normal or injured, this condition lies somewhere between these two conditions. The most significant adaptive changes in cells include atrophy (decreased cell size), hypertrophy (increased cell size), hyperplasia (increased cell number), and metaplasia (reversible replacement of one mature cell for another less mature cell or change in phenotype). Dysplasia (a disorder of cellular growth) is not considered a true cellular adaptation but rather an atypical hyperplasia. In conclusion, cellular adaptation is a central and common part of many disease conditions.